Butyrate Improves the Metabolic Disorder and Gut Microbiome Dysbiosis in Mice Induced by a High-Fat Diet - Gao, Feng; Lv, Yi-Wei; Long, Jie; Chen, Jie-Mei; He, Jiu-ming; Ruan, Xiong-Zhong; Zhu, Hai-bo (Frontiers in Pharmacology, 2019)
Abstract Background: Metabolic syndrome (MS) is one of the major cause of cardiovascular diseases(CAD). Gut microbiome diversity and its natural fermentation products are not only correlated with MS and CAD but also appear to be stronger than the associations of traditional risk factors. Therefore, the aim of this study was to provide a new potential pathway for natural fermentation product butyrate to improve metabolic syndrome and to examine whether associated with the serum metabolic profiles and gut flora composition. Method: C57BL/6 mice fed a high-fat diet were treated with 400mg/kg of sodium butyrate for 16 weeks. Blood and fecal samples were collected and measured with LC-MS and Illumina platform. The plasma differential metabolites and gut microbiome composition were analyzed with XCMS online and QIIME 2. Results: Gut microbiome-derived butyrate improved glucose intolerance and insulin resistance, resisting high-fat diet(HFD)-induced an increase of the relative abundance of f_Lachnospiracease, f_Rikenellaceae, and f_Paraprevotellaceae. Meanwhile, sodium butyrate increased the levels of α-linolenate, all-trans-retinal, resolvin E1, and leukotriene in the plasma and the differential pathways were mainly enrichment in resolvin E biosynthesis, histidine degradation, lipoxin biosynthesis, and leukotriene biosynthesis. Moreover, sodium butyrate can increase the levels of phosphorylated-adenosine 5‘-monophosphate (AMP)-activated protein kinas (p-AMPK) and facilitated glucose transporter member 4 (GLUT4) in adipose tissue. Conclusion: Butyrate can induce AMPK activation and GLUT4 expression in the adipose, improving cardiovascular disease-related metabolic disorder, resisting HFD- induced gut microbiome dysbiosis, and promoting resolvin E and lipoxin biosynthesis. Oral supplement of natural fermentation product butyrate can be a potential strategy for preventing cardiovascular diseases. KEYWORDS: AMPK, GLUT-4, Metabolomics, Sodium butyrate, 16s rRNA sequencing